2023
DOI: 10.1101/2023.03.29.534669
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

FADD- and RIPK3-mediated cell death ensures timely clearance of wound macrophages and promotes wound healing

Abstract: Cells of the monocyte/macrophage lineage are an integral component of the body's innate ability to restore tissue function after injury. In parallel to mounting an inflammatory response, clearance of monocytes/macrophages from the wound site is critical to re-establish tissue functionality and integrity during the course of healing. The role of regulated cell death in macrophage clearance from damaged tissue and its implications for the outcome of the healing response is little understood. Here, we explored th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…To further validate the role of cFLIP cleavage in protecting tissues from cell death–induced damage, we used a model of mouse full-thickness excisional skin injury. Because Caspase-8 was reported to play a crucial role in the wound healing response ( 45 ) and it was very recently shown that wound healing is a TNF- and cell death–dependent process ( 46 ), we wondered whether Caspase-8–mediated cFLIP cleavage could contribute to wound closure. The wound closure is characterized by the formation of the granulation tissue in the damaged area that is composed of different cell types whose concerted action promotes wound closure ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To further validate the role of cFLIP cleavage in protecting tissues from cell death–induced damage, we used a model of mouse full-thickness excisional skin injury. Because Caspase-8 was reported to play a crucial role in the wound healing response ( 45 ) and it was very recently shown that wound healing is a TNF- and cell death–dependent process ( 46 ), we wondered whether Caspase-8–mediated cFLIP cleavage could contribute to wound closure. The wound closure is characterized by the formation of the granulation tissue in the damaged area that is composed of different cell types whose concerted action promotes wound closure ( Fig.…”
Section: Resultsmentioning
confidence: 99%